2023
DOI: 10.1037/dec0000197
|View full text |Cite
|
Sign up to set email alerts
|

Risky choice and memory for effort: Hard work stands out.

Abstract: When deciding between different courses of action, both the potential outcomes and the costs of making a choice should be considered. These costs include the cognitive and physical effort of the different options. In many decision contexts, the outcome of the choice is guaranteed but the amount of effort required to achieve that outcome is unknown. Here, we studied choices between options that varied in the riskiness of the effort (number of responses) required. People made repeated choices between pairs of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
3
1
Order By: Relevance
“…For the common described problems, participants were more risk seeking for the harder problems (increases in effort) compared to easier problems (decreases in effort). This pattern is opposite to the one in Mason et al (2022) in an experience-based task. Our results and the evidence of this gap highlight again that effort is being treated as a loss as people consistently take risks to avoid the certain, high-effort outcomes.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…For the common described problems, participants were more risk seeking for the harder problems (increases in effort) compared to easier problems (decreases in effort). This pattern is opposite to the one in Mason et al (2022) in an experience-based task. Our results and the evidence of this gap highlight again that effort is being treated as a loss as people consistently take risks to avoid the certain, high-effort outcomes.…”
Section: Discussioncontrasting
confidence: 89%
“…Some previous research has examined the risky effort in such experience-based decision making, where the probabilities and outcomes are learned through repeated experience with feedback (Rakow & Newell, 2010;Wulff et al, 2018). For example, one recent paper, using a similar clicking paradigm, found that people were overall risk averse for effort in experience, but were more risk seeking for easy-effort problems compared to harder-effort problems (Mason et al, 2022). The current study suggests that a description-experience gap also exists in risk preferences for effort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations